Infection prevention in pediatric anesthesia practice. Issue 11 (13th October 2017) - Martin, Lizabeth D.; Kallile, Michael; Kanmanthreddy, Siri; Zerr, Danielle M.
Summary: Healthcare‐associated infections are an important source of morbidity and mortality in pediatric patients. Anesthesiologists have a unique role in infection prevention. Hand hygiene and anesthesia workspace decontamination decrease infection rates in surgical patients. Standard protocols exist for insertion and handling of central lines, arterial lines, and regional procedures, which should be strictly adhered to in order to prevent infectious complications. Temperature control and timely administration of antibiotics contribute to the prevention of surgical site infections. Education, culture shift, staff engagement, and effective change management are necessary for successful implementation of infection prevention strategies.